Preparation of Peleted Ni-Pt/Zeolite for Conversion of Amyl and Isoamyl Alcohol to Hydrocarbon - Abdullah Abdullah; Triyono Triyono; Bambang Setiaji (Universitas Gadjah Mada, 2001)
Catalysts with Ni and Pt as active metals in peleted zeolite were used for conversion of amyl alcohol, isoamyl alcohol and their mixture to hydrocarbon compounds. The catalysts were prepared by impregnation the peleted zeolite in NiCl2.6H2O and PtCI4 solution, while stirring for 24 hours then followed by oxidation with 02 gas at 350 °C for 2 hours and reduced by hydrogen gas at 400 °C for 1 hour. Ni and Pt in catalysts were determined by MS, specific surface area, total pore volume and gas sorption analyzer NOVA-1000 determined pore radius average. Determination of catalysts acidity was carried out by absorption of ammonia method. The activity of catalysts was evaluated in a micro reactor by flow system. Experimental temperature by varied between 300 and 400 °C with the increment of 25 °C. Products were analyzed by gas chromatographic and mass spectrometric method. The result shows that Ni-Pt/zeolite is more active than Ni/zeolite can be used for converting all of the alcohol. Products for conversion are 2-pentene, 2-methyl-1-butene, 2-methyl-2-butene, cyclopentane, 3-methyl-1-butanaldehide and acetone. The highest conversion was observed on isoamyl alcohol (31.37%) at 400 °C.